Tindak Pidana Persetubuhan yang Dilakukan oleh Anak; Analisis Penegakan Hukum Berdasarkan Asas Ultimum Remedium - Widadi, Selamat; Zainuddin, Cholidi; Martini (IAIN Langsa, 2024)
Should be, the principle of Ultimum Remedium should be applied in the enforcement of law against crimes committed by children; however, in reality, in Decision Number: 9/Pid.Sus-Anak/2023/Pn Plg, this principle was not optimally implemented. This inconsistency raises issues regarding the ideal legal protection for children as offenders, particularly in cases of sexual offenses. A harsher treatment than expected can impact the psychological well-being of the child and undermine the more humane rehabilitation goals within the juvenile justice system. This study aims to analyze the enforcement of law regarding sexual offenses committed by children and to assess the basis for the judge's considerations in rendering a decision based on the principle of Ultimum Remedium. The methodology used is normative legal research with a case approach, where the primary data is derived from the Palembang District Court Decision Number: 9/Pid.Sus-Anak/2023/Pn Plg, supported by secondary and tertiary legal materials that are analyzed qualitatively. The research findings indicate that the law enforcement in this case imposed a prison sentence of 4 years along with a fine of Rp 50,000,000, with an alternative of 3 months of vocational training. In the judge's considerations, the basis cited was Article 81 paragraph (1) in conjunction with Article 76 D of the Child Protection Law, emphasizing both juridical and non-juridical aspects, although the application of the Ultimum Remedium principle was not enforced due to various aggravating factors.